La vida (antes de la vida) de don Gregorio Guadaña y otros personajes - Bonet Ponce, Clara (Avisos de Viena, 2021)
Laurence Sterne's The Life and Opinions of Tristram Shandy, Gentleman (1759-1767) stands as a landmark in universal literary memory for several reasons. One notable aspect is the narrative twist wherein the narrator's birth is delayed until Book III, with events and opinions recounted from the unborn fetus's perspective. However, this narrative maneuver finds precedent in Early Modern Spain, particularly in Antonio Enríquez Gómez's 1644 work El siglo pitagórico y vida de don Gregorio Guadaña, which introduces the first-person voice of the unborn child explicitly. This work, blending various genres and centered on the transmigrations of a soul through different characters, notably portrays the intrauterine life of its protagonist. This paper explores the significance of this narrative innovation within the picaresque genre, highlighting its departure from conventional storytelling norms and its exploration of prenatal existence.